SLC8A1 antisense RNA 1 suppresses papillary thyroid cancer malignant progression via the FUS RNA binding protein (FUS)/NUMB like endocytic adaptor protein (Numbl) axis. Issue 5 (2nd May 2022) - Xin, Yunchao; Shang, Xiaoling; Sun, Xiaoran; Xu, Guogang; Liu, Yachao; Liu, Yanbin
ABSTRACT: Papillary thyroid cancer (PTC) is one of the most prevalent endocrine malignancies and is associated with severe morbidity and high mortality. This study aimed to explore the role of long non-coding RNA (lncRNA) SLC8A1 antisense RNA 1 (SLC8A1-AS1) in the pathogenesis of PTC. In this study, we explored the function of SLC8A1-AS1 in PTC progression. We observed that the expression of SLC8A1-AS1 was downregulated in clinical PTC samples and PTC cell lines compared to that in normal controls. Cell counting kit (CCK)-8 assays demonstrated that the overexpression of SLC8A1-AS1 significantly reduced the proliferation of PTC cells. Consistently, apoptosis of PTC cells was enhanced by SLC8A1-AS1 overexpression. SLC8A1-AS1 overexpression attenuated the invasion and migration of PTC cells. Mechanistically, SLC8A1-AS1 maintained NUMB like endocytic adaptor protein (Numbl) mRNA stability by interacting with FUS RNA Binding Protein (FUS) in PTC cells. Depletion of Numbl reversed the inhibitory effect of SLC8A1-AS1 overexpression on PTC. Thus, we concluded that SLC8A1-AS1 suppresses PTC progression via the FUS/Numbl axis. Our findings provide novel insights into the mechanism underlying SLC8A1-AS1 attenuation of the malignant development of PTC, improving our understanding of the association between lncRNAs and PTC. SLC8A1-AS1 and FUS may be potential targets for PTC treatment. Graphical abstract: uf0001